Response of plant life forms and soil physical properties to near-natural restoration measures in alpine grassland, Tibetan plateau - He, Guoxing; Liu, Xiaoni; Li, Yali; Ji, Tong (Frontiers in Plant Science, 2025)
IntroductionNear-natural restoration measures enhance the stability of plant life forms in degraded grasslands, facilitating the natural succession of plant communities.MethodsIn this study, we investigated the effects of three natural restoration measures on the alpine meadows of the northeastern Tibetan Plateau: banned grazing (BG), rest grazing (RG), traditional grazing (TG), and continuous grazing (CG). We utilized redundancy analysis (RDA), variation partitioning(VP), hierarchical partitioning (HP), and partial least squares pathway modeling (PLS-PM) to dissect the quantitative relationships between the distribution of plant life forms and soil physical properties under these restoration measures.Results and discussionThe results indicated the following: 1) Under each restoration measure, the distribution of life form plants were predominantly characterized by the highest number of hemicryptophytes, followed by geophytes, with the least number of therophytes. We found that the BG treatment had the highest hemicryptophyte height, coverage, aboveground biomass, and importance value, while the CG treatment had the lowest. 2) After near-natural restoration, the soil bulk density (BD) was decreased. The soil moisture characteristics (MC) were increased including soil saturated water content(SSWC), capillary water holding capacity (CWHC), field water capacity (FWC). And capillary porosity (CP) and non-capillary porosity (NP) were increased. 3) VP analysis revealed that MC, BD, and CP together explained 57.4% of the variation in plant life forms communities. 4) The hemicryptophytes benefited from restoration measures and increased CP. In contrast, the decrease in BD negatively affected geophytes. In summary, restoration measures reduce BD by enhancing MC and increasing CP, which affects the distribution of plant life forms. This finding reveals the important role of soil physical properties in plant survival strategies during alpine meadow restoration.